Pengaruh Lingkungan Fisik Sekolah Terhadap Perilaku Bullying: Sebuah Tinjauan Sistematis - Amal, Citra Amalia; Rumata, Nini Apriani (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
The physical environment of schools plays a crucial role in shaping students' social behaviour, including the prevention of bullying. This study aims to evaluate the influence of school physical design on bullying through a Systematic Literature Review (SLR) approach. The review focuses on aspects of visibility, surveillance, and the application of Crime Prevention Through Environmental Design (CPTED) principles in school design. Literature was collected from databases such as ScienceDirect and Google Scholar, using the keyword “school bullying” within the 2014–2024 range. Selected studies are empirical research from the fields of social sciences, psychology, and health that explore the relationship between school physical design and bullying. Inclusion criteria consist of studies examining physical design focused on safety and surveillance, as well as their impact on reducing bullying. Non-empirical or irrelevant studies were excluded. The analysis shows that CPTED principles, such as enhanced visibility and natural surveillance, are effective in reducing bullying incidents. Open and well-supervised areas are proven to be safer than hidden spaces. Moreover, designs that support student comfort contribute to psychosocial well-being and help prevent future mental health risks. This review also presents CPTED-based school design illustrations as practical recommendations for supporting anti-bullying policies in educational settings.